2013
DOI: 10.1186/cc12796
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of helicopter emergency medical services compared to ground emergency medical services in traumatized patients

Abstract: IntroductionPhysician-staffed helicopter emergency medical services (HEMS) are a well-established component of prehospital trauma care in Germany. Reduced rescue times and increased catchment area represent presumable specific advantages of HEMS. In contrast, the availability of HEMS is connected to a high financial burden and depends on the weather, day time and controlled visual flight rules. To date, clear evidence regarding the beneficial effects of HEMS in terms of improved clinical outcome has remained e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 44 publications
4
99
0
4
Order By: Relevance
“…Several European studies report more advanced interventions in the prehospital environment with a HEMS physician led team. 3032 However, in the US the concept of HEMS has developed primarily to transport patients rapidly to a trauma center, most often without direct physician involvement. This has been reinforced by early studies demonstrating HEMS is not useful in US urban environments with proximity to trauma centers.…”
Section: Discussionmentioning
confidence: 99%
“…Several European studies report more advanced interventions in the prehospital environment with a HEMS physician led team. 3032 However, in the US the concept of HEMS has developed primarily to transport patients rapidly to a trauma center, most often without direct physician involvement. This has been reinforced by early studies demonstrating HEMS is not useful in US urban environments with proximity to trauma centers.…”
Section: Discussionmentioning
confidence: 99%
“…Early adopters, such as Germany and the United States, have been operating emergency medical helicopters since 1970 [1], and HEMS have become an important component of pre-hospital care for trauma patients in many countries [25]. HEMS can provide faster transport of severely injured patients to highly specialized facilities than ground emergency medical services (GEMS).…”
Section: Introductionmentioning
confidence: 99%
“…No one could accurately estimate the time associated with these challenges and rather than provide our estimate we only present the objective figures to which any analyst can then apply an offset to add/subtract time thought to be appropriate to give a better estimation. It has been shown that patients requiring HEMS will require greater on-scene management and this may be the most reasonable explanation of difference in times [17]. The figure of 8.3 min in favour of ground transport implies that it would only take a delay of \10 min to be associated with any of the potential logistical challenges to justify activation of MEDEVAC112 as the appropriate response for the time critical management of these missions.…”
Section: Discussionmentioning
confidence: 95%
“…Finally the analysis of the cross catchment transfer of patients is an important point to address as it has some potentially important contribution to policy decisions. Firstly, with the provision of this excellent service, the hospitals that provide a dedicated helipad are subject to trauma cases that by their very nature demand greater manpower at the Emergency Department level, on-call radiology services and theatre time as well as an associated significant length of stay [4,17]. Resources to account for this should be apportioned appropriately at a national scale.…”
Section: Discussionmentioning
confidence: 99%